Online identity construction: How gamers redefine their identity in experiential communities. Issue 6 (4th November 2015) - Costa Pinto, Diego; Reale, Getúlio; Segabinazzi, Rodrigo; Vargas Rossi, Carlos Alberto
Abstract: This research aims to understand how gamers redefine their identity by extending, aggregating, and assembling the different dimensions of the self in experiential online communities. The authors conducted a series of filmed in‐depth and in game individual interviews, group interviews, informal conversations, and observation of online game sessions. A framework of online identity construction shows how gamers assemble their identities combining different self‐dimensions, using two different strategies: self‐extension and self‐aggregation. Self‐extension strategies consist in the idealization, development, and manipulation of avatars (their digital self). Self‐aggregation strategies refer to group participation and sharing virtual possessions within groups of players. To bring their identities from the experiential community to the real life, gamers combine these strategies by assembling and materializing identities. This framework has theoretical implications for the self, identity, and sharing in online contexts. Finally, the paper considers managerial implications and future research directions in online communities. Copyright © 2015 John Wiley & Sons, Ltd.